Role of Denture Base Resins in Prosthodontics and Its Advancement: An Umbrella Review - Singh, Rohit Kumar; Nallaswamy, Deepak; Rajeshkumar, Shanmugam; Varghese, Sheeja S; Sengupta, Chandan (Journal of Neonatal Surgery, 2025)
Background: Denture base resins play a critical role in prosthodontics, contributing to the restoration of oral function and aesthetics in edentulous and partially edentulous patients. Poly Methyl Methacrylate (PMMA) remains the material of choice; however, its limitations, such as poor mechanical strength and cytotoxicity, have driven research into newer advancements. Objective: This systematic review aims to summarize advancements in denture base resins, analyze their properties, and highlight future trends. Methods: A systematic search Title of PubMed, Scopus, and Web of Science databases was conducted using keywords such as "denture base resins," "PMMA," "reinforced acrylic resins," and "nanoparticle reinforcement." Studies published between 2000 and 2023 were included. The PRISMA flowchart guided the study selection process. Results: From 580 records identified, 16 studies met the inclusion criteria. Reinforcements with fibers (e.g., glass, carbon) and nanoparticles (e.g., titanium dioxide, zirconium) significantly improved the mechanical properties of PMMA. Microwave curing and light-activated resins also showed better dimensional stability and curing efficiency compared to conventional methods. Biocompatibility advancements focused on reducing residual monomer toxicity. Conclusions: Recent advancements in denture base resins, particularly fiber and nanoparticle reinforcements, have improved mechanical properties and biocompatibility. Future trends include 3D printing and smart materials for personalized prosthetics.